Recommendation to improve chronic kidney disease management guideline in primary healthcare, KwaZulu-Natal - Verosha Ramkelawan; Pretty N. Mbeje; Ntombifikile G. Mtshali (Curationis)
Background: The prevalence of chronic kidney disease (CKD) is high in KwaZulu-Natal (KZN), especially in individuals with risk factors such as HIV, diabetes mellitus and hypertension. Despite existing guidelines, the study identified multifactorial gaps in implementing CKD management measures at the primary healthcare (PHC) level. This leads to late-stage diagnoses and increased burdens on tertiary institutions, as identified in institutional statistics. The study was therefore conducted in four different settings: a tertiary hospital in Durban and three PHC centres across KZN (two urban centres and one in a township).